β-Lactoglobulin and Glycodelin: Two Sides of the Same Coin? - Sawyer, Lindsay (Frontiers in Physiology, 2021)
The two lipocalins, β-lactoglobulin and glycodelin, are possibly the most closely related members of the large and widely distributed lipocalin family, yet their functions appear to be substantially different. Indeed, the function of β-lactoglobulin, a major component of ruminant milk, is still unclear although neonatal nutrition is clearly important. On the other hand, glycodelin has several specific functions in reproduction conferred through distinct, tissue specific glycosylation of the polypeptide backbone. It is also associated with some cancer outcomes. The glycodelin gene, PAEP, reflecting one of its names, progestagen-associated endometrial protein, is expressed in many though not all primates, but the name has now also been adopted for the β-lactoglobulin gene (HGNC, www.genenames.org). After a general overview of the two proteins in the context of the lipocalin family, this review considers the properties of each in the light of their physiological functional significance, supplementing earlier reviews to include studies from the past decade. While the biological function of glycodelin is reasonably well defined, that of β-lactoglobulin remains elusive.